(3GdUdM GdLfGFj hCKQg aj GdOYhi GdYGeI (B=s Criminal settlement and its impact on the general case - (3GdeHjVjf, Ydj eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2015)
(3jJfGhd cJGH (B((3GdUdM GdLfGFj hCKQg aj GdOYhi GdYGeI (B= Criminal settlement and its impact on the general case) (3hGdPj bGe HJCdjag Ydj eMeO GdeHjVjf aj MhGdj (B(304) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdUdM(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd (B: (3GdCMcGe GdYGeI ddUdM GdLfGFj, GdaUd GdChd (B: (3eGgjI GdUdM GdLfGFj, GdaUd GdKGfj (B: (3eDjOGJ GdUdM GdLfGFj, GdaUd GdKGdK (B: (3fWGb GdUdM GdLfGFj, GdHGH GdKGfj (B: (3JWHjbGJ GdUdM GdLfGFj aj GdJTQjY GdCQOfj, GdaUd GdChd (B: (3GdJUGdM GdLeQcj hGdJUGdM GdVQjHj aj GdJTQjY GdCQOfj, GdaUd GdKGfj (B: (3JWHjbGJ NGUI ddUdM GdLfGFj aj GdJTQjY GdCQOfj GdaUd GdKGdK (B: (3eOi EecGfjI GdJhSY aj GdCNP HfXGe GdUdM GdLfGFj aj GdJTQjY GdCQOfj, Ke jfJgj HbGFeI GdeUGOQ(B. s
(3GdCUd CWQhMI eGLSJjQ(B-(3GdLGeYI GdCQOfjI, GdCQOf(B.s
(3JUeje (B: (3GdKbGaI ddJUeje hGdENQGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B299-304.s
Keywords: (3GdUdM (B((3bGfhf LfGFj(B)s -- (3GdCQOfs; (3bGfhf GdELQGAGJ GdLfGFjIs -- (3GdCQOfs; (3GdOYhi GdLfGFjIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs